Transcatheter valve‐in‐ring implantation of a repositionable valve system for treatment of severe mitral regurgitation. Issue 6 (23rd December 2015) - Lauterbach, Michael; Sontag, Bruno; Paraforos, Alexandros; Friedrich, Ivar; Hauptmann, Karl‐Eugen
Abstract : Introduction: Years after mitral valve surgery, progressive degeneration of reconstructed mitral valves or bioprostheses might lead to severe mitral valve regurgitation. Patients with significant comorbidity, or impaired left ventricular function are poor candidates for redo surgery at an acceptable risk at that later time point. Methods and results: This study reports the first‐in‐man transapical valve‐in‐ring implantations in the mitral position of the fully repositionable Lotus valve system approved for transcatheter aortic valve replacement in Europe. Transapical valve‐in‐ring implantations with this valve system were successfully performed in a 64‐year‐old female, and a 53‐year‐old male patient. Both patients were NHYA class IV, and carried an unacceptably high risk of cardiac surgery due to clinical condition and comorbidity. The first patient was successfully implanted a 25 mm valve, improved to NYHA class II, and was discharged 2 weeks after the procedure. The second patient required a short episode of cardiopulmonary resuscitation after valve implantation (27 mm), and was placed on veno‐venous ECMO for 24 hr to improve oxygenation. He developed stroke on day 7, and deceased from fatal, toxic rhabdomyolysis 13 days after the procedure. Conclusion: Transapical valve‐in‐ring implantation of the repositionable Lotus valve system in the mitral position is a feasible and promising option that merits further evaluation. © 2015 Wiley Periodicals, Inc.